Noncontrast dynamic 3D intracranial MR angiography using pseudo‐continuous arterial spin labeling (PCASL) and accelerated 3D radial acquisition. Issue 5 (15th October 2013) - Wu, Huimin; Block, Walter F.; Turski, Patrick A.; Mistretta, Charles A.; Rusinak, David J.; Wu, Yijing; Johnson, Kevin M.
<x xml:space="preserve">Abstract</x> Purpose To develop a novel dynamic 3D noncontrast magnetic resonance angiography (MRA) technique that combines dynamic pseudo‐continuous arterial spin labeling (dynamic PCASL), accelerated 3D radial sampling (VIPR), and time‐of‐arrival (TOA) mapping to provide quantitative assessment of arterial flow. Materials and Methods Digital simulations were performed to investigate the effects of acquisition scheme and sequence parameters on image quality and TOA mapping fidelity. Five patients with vascular malformations (arteriovenous malformation [AVM] = 3, dural arteriovenous fistula [DAVF] = 2) were scanned and the images were compared to digital subtraction angiography (DSA) for the ability to identify the arterial supply, AVM location, nidus size, and venous drainage. Results Digital simulations demonstrated reduced image artifacts and improved TOA accuracy using radial acquisition over Cartesian. TOA mapping accuracy is more sensitive to sampling window length than time spacing. Dynamic PCASL MRA depicted seven of eight arterial pedicles, and accurately measured the AVM nidus size when the nidus was compact. The venous drainage in the AVM patients was not consistently visualized. Conclusion Dynamic 3D PCASL‐VIPR with TOA mapping is able to acquire both high temporal and spatial resolution inflow dynamics that could improve diagnosis of high‐flow intracranial vascular diseases. J. Magn. Reson. Imaging 2014;39:1320–1326. © 2013 Wiley Periodicals, Inc.